Response to intervention within a multi-tiered systems of support: a missing element in the literacy curricula, policies, and practices in the Philippines - Bautista, Jude Cañero (Frontiers in Education, 2025)
International assessments in reading appear to be a strong driver of educational efforts within nations who participate in these tests. While some countries debate the declaration of educational crises within their jurisdictions based on these assessments, the case of the Philippines’ performance appear to be collectively recognized by Filipinos as existent, and therefore, needs to be boldly confronted. Correspondingly, educational reforms were made, but evidence-based decisions are yet to be seen. This brief argues that revisiting the research evidence is vital for policy and curricular changes so that factors are identified, and consequently, analyzed once progress monitoring shows how powerful or weak they are in influencing students’ literacy outcomes. This brief ultimately recommends the potential for a response to intervention within multi-tiered systems of support.